Considering the Diverse Views of Ecologisation in the Agrifood Transition: An Analysis Based on Human Relationships with Nature. (December 2022) - Magda, Danièle; Lamine, Claire; Billaud, Jean-Paul
This article aims to characterise the visions of ecologisation found within scientific approaches embraced by different epistemic communities, and which have inspired empirical work and public action on agrifood system transitions. Based on comparative readings of works anchored in our two disciplinary fields (ecology and sociology), we identified six large ensembles of epistemic communities as well as their points of convergence and divergence. We identify six ideotypical visions of ecologisation based on the types of 'relationships to nature' embedded in these large sets of epistemic communities: protectionism, functionalism, structuralism, post-structuralism, relational and pragmatist-experience-based. We suggest that pragmatist-experience-based approaches allow us to transcend two classical oppositions: between realism and constructivism, and between a conception of nature as passive and external as opposed to active and relational. Without claiming to offer a detailed analysis of these approaches, we hope that our work can be used as a tool to support reflection among scientists and other actors involved in agrifood system transitions.